The effect of metformin on viability and mitochondrial status of tumor and non-tumor cell line - Ljubičič, Jelena; Pešić, Andrej; Isaković, Anđelka (Medicinski podmladak, 2022)
Abstract Introduction: Metformin is a drug of choice in the therapy of type II Diabetes mellitus. There is a growing evidence of metformin's antitumor activity, but the suggested mechanisms of such activity are still not fully elucidated.The aim: To investigate the effect of therapeutic doses of metformin on viability and mitochondrial status of human non-small cell lung carcinoma (NCI-H460) and human immortalized lung fibroblasts (MRC-5) cell lines.Material and methods: Acid phosphatase and Crystal Violet assays were used for the determination of NCI-H460 and MRC-5 cell viability after the treatment with metformin (10-60 µM) for 1-7 days. Mitochondrial membrane potential, production of reactive oxygen species and superoxide anion, as well as mitochondrial mass were measured using flow cytometry after the treatment of the cells for 3, 24 and 120 h, followed by staining with appropriate fluorochromes: JC-1, DHR, DHE and Mitotracker Red.Results: Metformin didn't change the viability of both NCI-H460 and MRC-5 cells in all investigated time-points and all used concentrations. Depolarization of mitochondrial membrane was observed 3 h post-treatment in MRC-5 cells. Prolonged treatment (120 h) increased superoxide anion production and mitochondrial mass in NCI-H460 cells. No significant changes in production of reactive oxygen species were observed in both cells lines after short or extended exposure to metformin.Conclusion: Therapeutic concentrations of metformin don't influence the viability of NCI-H460 and MRC-5 cells, but induce mitochondrial depolarization after short-term exposure in lung fibroblasts and increase production of superoxide anion and mitochondrial mass in lung carcinoma cells after prolonged treatment.
Keywords: metformin, lung carcinoma, mitochondria